RESPON PERTUMBUHAN BIBIT ANGSANA (Pterocarpus indicus Willd.) TERHADAP MEDIA TUMBUH, PEMOTONGAN AKAR LATERAL DAN PEMBERIAN URIN SAPI Response of Angsana (Pterocarpus indicus Willd.) Seedling on Growing Media, Lateral Roots Cutting, and Cow’s Urine - Hariadi Saputra; Yadi Setiadi; Iwan Hilwan (Jurnal Silvikultur Tropika, 2017)
Nursery is a process in producing good quality seedlings. Seedling quality is determined by physical-physiological quality including woody stem, health, height, diameter, number of leaves, leaf color and compactness of media. The quality of angsana seedlings in this study was observed using some growth media, lateral root cutting, and cow’s urine addition with various concentration and liquid organic fertilizer for 13 weeks. The study was conducted in a completely randomized design (CRD) in split plot with 3 growth mediums, 10 combinations of root-cutting and fertilizing treatment using 9 seedlings per treatment. Parameters observed during this study were seedling height (cm), seedling diameter (mm), total dry weight (g), shoot - root ratio (RPA) and compactness of roots. The results showed the media contain mixture of soil and manure (M2) with root-cutting treatment, addition of 20% cow urine and 5% EM4 (A2) was the best treatment for angsana seedlings with average value of 46.25 cm plant height, 6.09 mm diameter, 7.77 g total dry weight, shoot root ratio 1.89 and compactness of roots including the compact category.Key word : cow’s urine, lateral roots cutting, Pterocarpus indicus Willd., seedling quality.